2007
DOI: 10.1080/02713680701294723
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue versus Vicryl Sutures for Primary Conjunctival Closure in Pterygium Surgery: Long-Term Results

Abstract: The use of fibrin glue in pterygium surgery significantly reduces operative time and patient pain compared with suturing. However, it may be associated with a higher recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 27 publications
7
43
2
6
Order By: Relevance
“…These findings were also consistent with the studies of CA using fibrin glue, in which a number of different symptom scales have been used. [4][5][6][7][8] Shortening the surgery time and improving post-operative comfort may have several advantages. First, the use of fibrin glue removes the need for the tedious suturing process, the learning curve can be shortened, and better results may be more consistently achieved despite differences in surgical expertise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were also consistent with the studies of CA using fibrin glue, in which a number of different symptom scales have been used. [4][5][6][7][8] Shortening the surgery time and improving post-operative comfort may have several advantages. First, the use of fibrin glue removes the need for the tedious suturing process, the learning curve can be shortened, and better results may be more consistently achieved despite differences in surgical expertise.…”
Section: Discussionmentioning
confidence: 99%
“…This effort to mask the patients was also performed in earlier studies. [5][6][7][8] When fibrin glue is used, the retraction of the host conjunctiva or graft may result in gap formation between the graft in the early post-operative period. It is suggested that rapid epithelisation of the amniotic membrane prevents post-operative inflammation and thereby reduces the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various different studies have compared the safety and recurrence rates of pterygium associated with the use of absorbable and non-absorbable sutures and the use of sutures and fibrin glue when making conjunctival autografts (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . All of these studies concluded that the use of fibrin glue in pterygium surgery involving conjunctival autografting significantly reduces surgery time and improves postoperative patient comfort and cosmesis.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies concluded that the use of fibrin glue in pterygium surgery involving conjunctival autografting significantly reduces surgery time and improves postoperative patient comfort and cosmesis. Even so, there was no such consensus with respect to the question of recurrences and unfortunately, the recurrence rate was not evaluated in many of these studies (7,9,10,14,16,18) . Some studies did, however, demonstrate lower rates of recurrence when fibrin glue was used (8,13) , while in others, the same rate of recurrence was reported as associated with suturing (10,11,(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%